x(t) = -u(t-3)+2u(t+1)-2u(t-1)+u(t-3)
30 views (last 30 days)
Show older comments
x(t) = -u(t-3)+2u(t+1)-2u(t-1)+u(t-3)
how to solve it ? help i'm new
0 Comments
Answers (1)
Jonas
on 8 Feb 2023
please check your given equation, the last and first term cancel out each other. Nevertheless, i kept both of them in the code below
generate a time vector from -5 to 5 with step 0.1
t=-5:0.1:5;
generate unit step data
x=zeros(size(t));
preFactors=[-1 +2 -2 +1];
timeShifts=[-3 +1 -1 -3];
for termNr=1:numel(preFactors)
% create current unit impulse
thisTerm=t>-timeShifts(termNr);
% add up
x=x+preFactors(termNr)*thisTerm;
end
stem(t,x,'.')
0 Comments
See Also
Categories
Find more on Mathematics and Optimization in Help Center and File Exchange
Community Treasure Hunt
Find the treasures in MATLAB Central and discover how the community can help you!
Start Hunting!